In vivo alpha-V beta-3 integrin expression in human aortic atherosclerosis. Issue 24 (17th August 2019) - Jenkins, William S; Vesey, Alex T; Vickers, Anna; Neale, Anoushka; Moles, Catriona; Connell, Martin; Joshi, Nikhil Vilas; Lucatelli, Christophe; Fletcher, Alison M; Spratt, James C; Mirsadraee, Saeed; van Beek, Edwin JR; et al.
Abstract : Objectives: Intraplaque angiogenesis and inflammation are key promoters of atherosclerosis and are mediated by the alpha-V beta-3 (αv β3 ) integrin pathway. We investigated the applicability of the αv β3 -integrin receptor-selective positron emission tomography (PET) radiotracer 18F-fluciclatide in assessing human aortic atherosclerosis. Methods: Vascular 18F-fluciclatide binding was evaluated using ex vivo analysis of carotid endarterectomy samples with autoradiography and immunohistochemistry, and in vivo kinetic modelling following radiotracer administration. Forty-six subjects with a spectrum of atherosclerotic disease categorised as stable (n=27) or unstable (n=19; recent myocardial infarction) underwent PET and CT imaging of the thorax after administration of 229 (IQR 217–237) MBq 18F-fluciclatide. Thoracic aortic 18F-fluciclatide uptake was quantified on fused PET-CT images and corrected for blood-pool activity using the maximum tissue-to-background ratio (TBRmax ). Aortic atherosclerotic burden was quantified by CT wall thickness, plaque volume and calcium scoring. Results: 18F-Fluciclatide uptake co-localised with regions of increased αv β3 integrin expression, and markers of inflammation and angiogenesis. 18F-Fluciclatide vascular uptake was confirmed in vivo using kinetic modelling, and on static imaging correlated with measures of aortic atherosclerotic burden: wall thickness (r=0.57, p=0.001), total plaque volume (r=0.56, p=0.001) and aortic CT calcium score (r=0.37, p=0.01). Patients with recent myocardial infarction had greater aortic 18F-fluciclatide uptake than those with stable disease (TBRmax 1.29 vs 1.21, p=0.02). Conclusions: In vivo expression of αv β3 integrin in human aortic atheroma is associated with plaque burden and is increased in patients with recent myocardial infarction. Quantification of αv β3 integrin expression with 18F-fluciclatide PET has potential to assess plaque vulnerability and disease activity in atherosclerosis.